PENGARUH DISPLAY PRODUCT TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PT. ACE HARDWARE SIDOARJO - Hefry Wika Kusuma Wardhana; Ainur Rochmaniah (Kanal: Jurnal Ilmu Komunikasi, 2012)
A company that engages in the retail home furnishings that is rapidly evolving to have 98 branches / outlets spread across cities in Indonesia is PT. Ace Hardware Indonesia.Tbk. PT. Ace Hardware Sidoarjo is the 39th branch which was established in 2008. PT. Ace Hardware Sidoarjo is always trying to create a good image for their company along with the professional services market segment for the middle class and above with reasonable and competitive price, so that it will improve profitability significantly while understanding the part of the marketing concept. This study is aimed to analyze the effect of display products towards purchase decisions of the consumers of PT. Ace Hardware Sidoarjo. Respondents involved in this study were 100 respondents, with a purposive sampling method. Questionnaire data collection and analysis methods of quantitative analysis performed by simple linear regression using SPSS software for windows 16:00. From the results of the regression test, it was shown that variable has weak influence on the purchase decision variables. So, we can get the summary that the display product does not affect consumer’s purchase decision.